Prospects for innovative development of the Russian oil and gas complex in the context of modern challenges - A. V. Otvetchikov (Вестник университета)
The purpose of  the article is   to study the opportunities of   innovative development of  the Russian oil and gas complex amid current challenges. The subject of   the article is   modern features of  functioning of   the Russian oil and gas sector. As a   methodology, it  is necessary to   high-light the analysis of   Internet resources and articles relevant to   the research topic, statistical data, their synthesis and generalisation. Among the main results of   the work we  will indicate structuring sanctions in   terms of   the direction of   impact on  innovation activities, identifying opportunities and prospects for innovative development of   companies in   the oil and gas sector in   the current conditions. The results obtained can be  applied as  part of   assessing the prospects with consideration to  the modern situation and in  the educational process. The directions for further research on a  given topic include studying the operating features of   companies of   various sizes during their activities as   well as   identifying the most effective technological designs that can be   used in   the industry, including domestic ones. We   have made the following main conclusions. Firstly, the impact of   the sanctions is   aimed largely at  the technological development of   oil and gas companies. Secondly, the prohibitive measures have stimulated the use and implementation of  domestic innovations. Thirdly, the application of   new decisions makes it  possible to  optimise the processes of   the technological development, including those that until recently were determined to   be unprofitable. Fourthly, innovations help to  increase the number of  organisations in  the oil and gas sector by   involving small-sized companies whose activities cover a  minor segment that is  not attractive to  large corporations.